2014
DOI: 10.7554/elife.01828
|View full text |Cite
|
Sign up to set email alerts
|

ERK8 is a negative regulator of O-GalNAc glycosylation and cell migration

Abstract: ER O-glycosylation can be induced through relocalisation GalNAc-Transferases from the Golgi. This process markedly stimulates cell migration and is constitutively activated in more than 60% of breast carcinomas. How this activation is achieved remains unclear. Here, we screened 948 signalling genes using RNAi and imaging. We identified 12 negative regulators of O-glycosylation that all control GalNAc-T sub-cellular localisation. ERK8, an atypical MAPK with high basal kinase activity, is a strong hit and is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 63 publications
(108 reference statements)
1
66
0
Order By: Relevance
“…A potential role for cytosolic PCNA in cellular signaling. Schematic overview of known connections between the pattern recognition receptors TLRs, PKR and RIG-1 (illustrated in dark blue) and the PI3K/Akt, MAPK and NFκB signaling pathways [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]32,[37][38][39][40][41]57,58,68,69,71,78,79]. Proteins containing the APIM-sequence associated with these pathways are illustrated in pink [11].…”
Section: Isolation and Stimulation Of Peripheral Blood Monocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential role for cytosolic PCNA in cellular signaling. Schematic overview of known connections between the pattern recognition receptors TLRs, PKR and RIG-1 (illustrated in dark blue) and the PI3K/Akt, MAPK and NFκB signaling pathways [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]32,[37][38][39][40][41]57,58,68,69,71,78,79]. Proteins containing the APIM-sequence associated with these pathways are illustrated in pink [11].…”
Section: Isolation and Stimulation Of Peripheral Blood Monocytesmentioning
confidence: 99%
“…three direct members of the PI3K/Akt pathway (p110-α, p110-γ, and PI3K-C2β), proteins regulating PTEN (MAST3 and PLK3), and proteins of the mitogen-activated protein kinase (MAPK) pathways (ERK8, MK2, MK5, MST4, SOS1, NF1, and TAO1 and 2) [13][14][15][16][17][18][19][20] (see pink proteins in Fig. 1).…”
Section: Introductionmentioning
confidence: 98%
“…Low to moderate expression levels of MAPK15 are detected in normal tissues, such as breast, lung, liver, stomach, colon, and kidney [12,13] . In addition, Chia et al reported that MAPK15 downregulation in breast and lung carcinomas can drive the cancers aggressively by activating cell motility [14] . In contrast, MAPK15 is highly expressed in anaplastic thyroid carcinoma cell lines (ARO, Cal62, and Kat4) and a colon cancer cell line (HCT15) but is expressed at a very low level in the JB6 Cl41 normal mouse epidermal cell line [15,16] .…”
mentioning
confidence: 99%
“…Extensive arrays of specific ERK1/2, JNK, and p38 inhibitors have been evaluated in preclinical and clinical trials, but the value of a MAPK15 inhibitor to treat cancer has not been tested. Some studies have used Ro-318220 to inhibit MAPK15 kinase activity but this molecule is a typical selective protein kinase C inhibitor [14,24,33] . A three-dimensional analysis of the MAPK15 domain revealed a high percentage of scaffolds to develop specific kinase inhibitors [34] .…”
mentioning
confidence: 99%
See 1 more Smart Citation